Effect of Probiotics on Glycemic Control: A Systematic Review and Meta-Analysis of Randomized, Controlled Trials. - Yuting Ruan; Jia Sun; Jie He; Fangyao Chen; Rongping Chen; Hong Chen (PLoS ONE, 2015)
Background Previous clinical trials indicate that probiotic consumption may improve blood glucose control, however, results from randomized trials on glycemic control have been inconsistent. Objective To investigate the effects of probiotics on glycemic control in a systematic review and meta-analysis of randomized controlled trials. Data sources PubMed, Embase, Cochrane Library, and Clinicaltrial.gov through October 2014. Data extraction and synthesis Two independent reviewers extracted relevant data and assessed study quality and risk of bias. Data were pooled using a random-effects model and expressed as mean differences (MD) with 95% CI. Heterogeneity was assessed (Cochran Q-statistic) and quantified (I2). Results Seventeen randomized controlled trials were included, in which 17 fasting blood glucose (n = 1105), 11 fasting plasma insulin (n = 788), 8 homeostasis model assessment of insulin resistance (n = 635) comparisons were reported. Probiotic consumption, compared with placebo, significantly reduced fasting glucose (MD = -0.31 mmol/L; 95% CI 0.56, 0.06; p = 0.02), fasting plasma insulin (MD = -1.29 μU/mL; 95% CI -2.17, -0.41; p = 0.004), and HOMA-IR (MD = 0.48; 95% CI -0.83, -0.13; p = 0.007). Conclusions Probiotic consumption may improve glycemic control modestly. Modification of gut microbiota by probiotic supplementation may be a method for preventing and control hyperglycemia in clinical practice.